2014
DOI: 10.3389/fpls.2014.00180
|View full text |Cite
|
Sign up to set email alerts
|

Two maize END-1 orthologs, BETL9 and BETL9like, are transcribed in a non-overlapping spatial pattern on the outer surface of the developing endosperm

Abstract: In the course of a project aimed to isolate transfer cells-specific genes in maize endosperm we have identified the BETL9 gene. BETL9 encodes for a small protein very similar in sequence to the product of the barley transfer cell-specific gene END-1. Both BETL9 and END-1 proteins are lipid transfer proteins, but their function is currently unknown. In situ hybridization analysis confirms that the BETL9 gene is exclusively transcribed in the basal endosperm transfer cell layer during seed development since 10 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…It was reported that expression of OsPR602, belonging to the same clade of OsLTPL36, was restricted to the aleurone cells located in closer proximity to the maternal vascular bundles, the main channel for nutrients transfer [33]. Our results showed that…”
Section: Osltpl36 Might Be a Lipid Transporter During Seed Developmensupporting
confidence: 49%
See 1 more Smart Citation
“…It was reported that expression of OsPR602, belonging to the same clade of OsLTPL36, was restricted to the aleurone cells located in closer proximity to the maternal vascular bundles, the main channel for nutrients transfer [33]. Our results showed that…”
Section: Osltpl36 Might Be a Lipid Transporter During Seed Developmensupporting
confidence: 49%
“…2H-I). Since rice seed has no distinct endosperm transfer cell layer [33]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17…”
Section: Osltpl36 Might Be a Lipid Transporter During Seed Developmenmentioning
confidence: 99%
“…In wheat and barley, transfer cells are a vascular bundle running along the length of the grain, through modified maternal cells in the nucellar projection, to the endosperm cavity that extends along the seed, in parallel to the vascular bundle (116) . The expression of TaALP in the transfer cells as well as aleurone cells under pathogen infection is consistent with the evidence that endosperm transfer cells maintain a delicate balance between nutrients transportation and the need to impede the ingress of pathogens into the developing seed (117) . Transfer cells are involved in delivery of nutrients between generations and in the development of reproductive organs and also facilitate the exchange of nutrients that characterize symbiotic associations (116) .…”
Section: Discussionsupporting
confidence: 84%
“…Enriched TaALP genes transcripts can also be localized in developing embryo around 15-18 DAP, which also indicate another category that might be of great interests. Proteomic study have indicated that proteins induced in response to infection are proteins involved in protein synthesis, folding and stabilization, as well as proteins involved in oxidative stress tolerance, and PR proteins in tissues of the fungal-infected germinating embryo ( 118 ). Lectin are known to have antifungal properties and are actively involved in plant defense, are expressed at low levels in the developing embryo together with the more abundant seed storage proteins ( 119 ).…”
Section: Discussionmentioning
confidence: 99%
“…These genes showed CS scores in the given compartments ranging from 0.47 to 0.99. Third, we summarized previously reported in situ hybridization or promoter activity data for cell-specific genes from the literature (Hueros et al, 1995(Hueros et al, , 1999Magnard et al, 2000Magnard et al, , 2003Serna et al, 2001;Woo et al, 2001;Gómez et al, 2002Gómez et al, , 2009Gutiérrez-Marcos et al, 2004;Wisniewski and Rogowsky, 2004;Balandín et al, 2005;Massonneau et al, 2005;Muñiz et al, 2006Muñiz et al, , 2010Royo et al, 2014) and also found these genes to have a relatively high range of CS scores (0.51 to 0.99). Altogether, these comprise 44 genes showing cell-specific expression in the endosperm (Supplemental Table 6).…”
Section: Identification Of Gene Sets Specifically Expressed In Each Omentioning
confidence: 99%